STRATEGI MEDIA RELATIONS DALAM MENDUKUNG PEMBANGUNAN TOL LISTRIK SULAWESI TAHAP 1 - Madia, Aidia Syafitri; Muh. Akbar; Indrayanti (AT-TAWASUL, 2025)
This research analyzes the media relations strategy implemented by PT PLN (Persero) South Sulawesi Development Parent Unit (UIP SulbagSel) in supporting the construction of the Sulawesi Electricity Highway Phase 1. This electricity infrastructure development aims to increase the capacity of energy supply in Sulawesi, which is expected to support economic growth and industrialization. In this context, media relations plays an important role in strengthening the company's image and ensuring the smooth running of the project. This research used a descriptive qualitative approach, with in-depth interviews, field observations, and documentation review as data collection methods. The research findings show that PLN UIP SulbagSel carries out media relations based on central regulations with a contextual and segmented strategy, which includes selecting media according to the type of information and audience. In addition, this strategy focuses on publicity, image management and crisis communication. With a structured planning approach, PLN UIP SulbagSel manages relationships with the media through systematic work planning and careful media mapping. The results of this study contribute to the development of communication theory and media relations practice in the context of major infrastructure development in Indonesia